Semicircle inscribed in a Quadrilateral

Geometry Level 3

The above semicircle is inscribed in quadrilateral A B C D ABCD and is tangent to the semicircle at points E , F E, F and G G and O A O D \overline{OA} \cong \overline{OD} and A B = a \overline{AB} = a and C D = b \overline{CD} = b as shown above.

Find A D a b \dfrac{\overline{AD}}{\sqrt{ab}} .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
May 18, 2021

A E O O G D \triangle{AEO} \cong \triangle{OGD} and 2 ( m + n + θ ) = 18 0 m + n + θ = 9 0 2(m + n + \theta) = 180^{\circ} \implies m + n + \theta = 90^{\circ} or m + n = 90 θ m + n = 90 - \theta .

O A B O B C a O B = O B a + b 2 x O B 2 = a ( a + b 2 x ) \triangle{OAB} \sim \triangle{OBC} \implies \dfrac{a}{\overline{OB}} = \dfrac{\overline{OB}}{a + b - 2x} \implies \overline{OB}^2 = a(a + b - 2x)

and

O D C O B C b O C = O C a + b 2 x O C 2 = b ( a + b 2 x ) \triangle{ODC} \sim \triangle{OBC} \implies \dfrac{b}{\overline{OC}} = \dfrac{\overline{OC}}{a + b - 2x} \implies \overline{OC}^2 = b(a + b - 2x)

Using the law of cosines on O B C \triangle{OBC} \implies

( a + b 2 x ) 2 = ( a + b 2 x ) ( a + b 2 a b cos ( m + n ) ) (a + b - 2x)^2 = (a + b - 2x)(a + b - 2\sqrt{ab}\cos(m + n)) \implies

a + b 2 x = a + b 2 a b cos ( m + n ) x = a b cos ( m + n ) = a b sin ( θ ) a + b - 2x = a + b - 2\sqrt{ab}\cos(m + n) \implies x = \sqrt{ab}\cos(m + n) = \sqrt{ab}\sin(\theta)

= z sin ( θ ) z = a b A D = 2 a b A D a b = 2 = z\sin(\theta) \implies z = \sqrt{ab} \implies \overline{AD} = 2\sqrt{ab} \implies \dfrac{\overline{AD}}{\sqrt{ab}} = \boxed{2} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...